PEMBERDAYAAN POKDARWIS DALAM PENGEMBANGAN WISATA SITUS WARISAN BUDAYA DI DESA ARJASA KABUPATEN JEMBER - Arif Arif; Michael Cristofer R; Moh. Rizqy Izzul Haaq; Nana Maulidya; Ubaid Farid Handoko; Winda Amilia (LP2M Universitas Jember, 2022)
People and culture are an inseparable, while the supporters of culture are the people themselves. Jember Regency has one of its cultural assets, namely the Calok site. The site is a relic of the Megalithic era. The calok site has the potential to become a cultural educational tourism destination. The tourism community Arjasa has pioneered the development of the Calok Site as a cultural education tourism destination, but this development has been slow due to the Covid-19 pandemic. The development of the Calok Site aims to introduce the existence of the Calok Site to the community in order to raise awareness of cultural preservation. The empowerment method is carried out by counseling and training on the development of the Pinching Site to tourism community and providing information media on the Pinching site for the community using a barcode. The results of this activity are the increased ability of tourism community to develop cultural tourism and the availability of information about the Calok Site.